2012
DOI: 10.1063/1.4736989
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of plasma plume evolution against ambient background gas in laser blow off experiments

Abstract: Two dimensional numerical modelling based on simplified hydrodynamic evolution for an expanding plasma plume (created by laser blow off) against an ambient background gas has been carried out. A comparison with experimental observations shows that these simulations capture most features of the plasma plume expansion. The plume location and other gross features are reproduced as per the experimental observation in quantitative detail. The plume shape evolution and its dependence on the ambient background gas ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Recently, we have simulated the lateral interactions between two spatially separated LBO plasma plumes in the presence of argon ambient [32]. In this approach, continuity, momentum and the energy equations of the ablated material are solved numerically in two dimensions (2D) [32,33]. In this numerical study, we showed the formation of shock waves and their interactions in argon ambient, which is in good agreement with experimental observations [32].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Recently, we have simulated the lateral interactions between two spatially separated LBO plasma plumes in the presence of argon ambient [32]. In this approach, continuity, momentum and the energy equations of the ablated material are solved numerically in two dimensions (2D) [32,33]. In this numerical study, we showed the formation of shock waves and their interactions in argon ambient, which is in good agreement with experimental observations [32].…”
Section: Introductionsupporting
confidence: 80%
“…We modeled the time evolution of the plasma plume in the ambient gas using basic fluid equations that include mass, momentum and energy equations [32,33].…”
Section: Basic Fluid Equationsmentioning
confidence: 99%